Study On Hydrolysis Of Polyvinyl Acetate To Polyvinyl Alcohol - Mathivanan, Vinessa (Universiti Sains Malaysia, 2018)
Polyvinyl alcohol, PVA is a biodegradable and water soluble polymer with vast application in various industries. In recent years, PVA hydrogels and blends have found wide application in the biomedical industry due to its high solubility property. The solubility of PVA is greatly affected by the degree of hydrolysis of the PVA. The presented research thesis studied the effect of different parameters such as reaction temperature, reaction time and the type of catalyst on the degree of hydrolysis of PVA. The hydrolysis reaction of polyvinyl acetate, PVAc was done with solvent methanol in the presence of alkali catalyst, sodium hydroxide, NaOH at temperatures 40, 60 and 80 'C and reaction times 30, 45 and 60 mins. For acid catalyst, hydrochloric acid, HCl the temperature and reaction time were set as 60 'C and 60 mins. Titration with acid or alkali respectively was done to determine the degree of hydrolysis of PVA. Both the temperature and reaction time were directly proportional to the degree of hydrolysis. Alkali catalyst produced more hydrolyzed PVA compared to acid catalyst at the same reaction conditions. The solubility of PVA increased with increasing degree of hydrolysis up to 91% hydrolysis and beyond that value the solubility decreased. Scanning Electron Microscope, SEM was used to study the surface morphology of PVA while Energy Dispersive X-Ray Analyzer, EDX was used to identify the components of PVA. From ANOVA analysis, the optimum temperature and reaction time to produce 97% hydrolyzed PVA is 79.93 'C and 59.91 mins.